2015
DOI: 10.1128/cvi.00460-15
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus IgG Level and Avidity in Breastfeeding Infants of HIV-Infected Mothers in Malawi

Abstract: dCytomegalovirus (CMV) infection is common among infants of HIV-infected mothers in resource-limited settings. We examined the prevalence and timing of infant CMV infection during the first year of life using IgG antibody and avidity among HIVexposed infants in Malawi and correlated the results with the presence of detectable CMV DNA in the blood. The Breastfeeding, Antiretrovirals and Nutrition (BAN) study randomized 2,369 mothers and their infants to maternal antiretrovirals, infant nevirapine, or neither fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
3
1
Order By: Relevance
“…One may assume that the CMV IgG in infants is derived from the mothers because of the transplacental transfer of maternal CMV IgG. However, our previous study and others demonstrated that the maternally acquired CMV IgG in infants disappears before the age of 6-8 months (4,18). In the present study, all infants were negative for CMV IgM at birth and were positive for CMV IgG over the age of 7 months.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…One may assume that the CMV IgG in infants is derived from the mothers because of the transplacental transfer of maternal CMV IgG. However, our previous study and others demonstrated that the maternally acquired CMV IgG in infants disappears before the age of 6-8 months (4,18). In the present study, all infants were negative for CMV IgM at birth and were positive for CMV IgG over the age of 7 months.…”
Section: Discussioncontrasting
confidence: 58%
“…Previous study showed that transplacentally transferred maternal CMV IgG in infants disappears before 6-8 months age because of the natural IgG decay (4,18). In the present study, all infants participated were over 7 months age, therefore, we measured the CMV IgG as a marker of CMV infection in the infants.…”
Section: Seroprevalence Of CMV Igg In Infants With Different Feeding ...mentioning
confidence: 82%
“…We also demonstrate evidence of HIV exposure and increased likelihood of hCMV exposure in HEU infants. HIV and hCMV are immunomodulatory viruses 81 , so co-exposure to these two pathogens in early life may contribute to this immune dysregulation. We postulate that the complexity, variable severity and/or persistence of this immunological phenotype explain the variable clinical manifestations reported in HEU infants 8,9,11,40,[82][83][84][85][86] , which may depend on the duration and intensity of exposure to HIV and other infectious co-factors.…”
Section: Discussionmentioning
confidence: 99%
“…CMV PCR testing in urine and saliva has very high sensitivity and specificity (>90%), compared with serological testing [38, 41]. Additionally, a recent study assessing the validity of PCR testing in blood found that PCR detected most infant CMV infections [40]. …”
Section: Discussionmentioning
confidence: 99%